Bioaccumulation of mercury by the panaeid prawns from Rushikulya estuary, east coast of India - Das, Snehalata (Indian Journal of Fisheries, 2011)
Commercially important penaeid prawns namely Penaeus monodon and Penaeusindicus from the waters of a tropical estuary along the east coast of India wereexposed for 96 hours down to different concentrations of HgCl^ at various salinities.The accumulation patterns of mercury were analysed at 24-hour interval withrespect to concentrations of 0.005 and 0.01 ppm and salinities of 5, 15 and 25psu in various body parts such as digestive tract, exoskeleton and muscle of theorganisms. The highest concentrations of mercury was observed in the digestivetract compared to other body parts and the order of accumulation was found tobe as digestive tract > exoskeleton > muscle with increase in concentrations andtime period for both the species. At salinity of 15 psu Hg content was highestwhile 25 psu was the lower than 15 psu but higher than 5 psu salinity indicating15 psu salinity as a favourable medium for Hg accumulation in each case. P.monodon was noticed to be more sensitive indicator organism than P. indicus